Presidential Candidate and Term of Office and Vice President in Indonesia - Sholehudin, Miftahus; Sukadi, Imam (PT. Riset Press International, 2025)
Article 7 of the 1945 Constitution of the Republic of Indonesia still has weaknesses. Its formulation can still be interpreted differently from the original intent , which emphasized the term limits of the president and vice president. The formulation of Article 7 of the 1945 Constitution of the Republic of Indonesia reads